Evolucion del juego en defensa en balonmano: hacia las defensas alternativas como concepto - de Dios Román Seco, J. (Revista Ciencia del Deporte, 2016)
People that study this sport modality have traditionally turned their attention, efforts, analysis and research into attack playing aspects and less regard to defensive playing. It has been understood, in a global way, that it is in the attack variables where the options to increase and improve the creativity of the game has its ideal location. Perhaps therein lies the main reason for the insufficient tactical and strategic evolution of the defensive playing in handball. The present article raises the need to improve the behaviors, the traditional ones and other technologies, in the content of the defensive playing not only as the enrichment of this task in itself as the essential factor for the evolution of the game. The wealth of handball, according to the author, is based on the principle, "the various defensive behaviors demand reactions in the attack playing" thus placing in the field of defensive playing the regulators of the game. The author exposes a rigorous methodological system in which the concepts of playing space and the moment of action are conjugated in an alternative way as base of the defensive complexity. It translates all into a philosophy of defensive behavior valid for any structure applicable to all times and circumstances.